KONSEP RESTORATIVE JUSTICE MELALUI MEDIASI PENAL DALAM PENYELESAIAN PERKARA PIDANA BERMOTIF RINGAN PADA MASYARAKAT ADAT KAMPUNG KUALA GASIB DI KECAMATAN KOTO GASIB KABUPATEN SIAK - ELMA YANTI (JURNAL HUKUM DAS SOLLEN, 2018)
The settlement of criminal offenses with mild motives can be carried out by reasoning penal mediation called the restorative justice approach, which focuses on the direct participation of perpetrators, victims and the community. The research that use in this study is sociological legal research (social legal research). The concept of restorative justice through reasoning penal mediation in the settlement of a mildly criminal case for the indigenous people of village kuala gasib in koto gasib siak, was carried out with the intermediary of the headman. Headman as customary village heads and as government administrators have an important role in creating peace efforts in resolving disputes that occur in the community, one of which is through the settlement of criminal cases by reasoning penal mediation with the concept of restorative justice. The constraints of the concept of restorative justice through reasoning penal mediation in the settlement of mildly criminal cases for the indigenous people of village kuala gasib in koto gasib siak are: a) The absence of a special law mediation of regulation, b) Lack of facilities and infrastructure in mediating, c) Lack of mediator skills for village head to reconcile the parties to the dispute, d) There are differences of opinion among law enforcement officials about the concept of restorative justice through penal mediation